2013
DOI: 10.1177/1352458513505351
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training is feasible in severely disabled patients with progressive multiple sclerosis

Abstract: This study tested whether upper-body endurance training (ET) is feasible and can be performed at sufficient intensity to induce cardiovascular adaptations in severely disabled patients with progressive multiple sclerosis (MS). Eleven progressive MS patients (6.5 ≤ EDSS ≤ 8.0) scheduled for a four-week inpatient rehabilitation program were randomized to a control group (CON, n = 5) that received standard individualized MS rehabilitation or an intervention group (EXE, n = 6) that in addition received 10 sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 8 publications
3
69
0
Order By: Relevance
“…A study conducted by Skjerbaek et al 20 tested the feasibility of upper-body endurance training among 11 individuals with progressive MS who were significantly affected by the adverse effects of the disorder. The researchers found that endurance training could be performed at sufficient intensity to procure cardiovascular adaptations and therefore was feasible for individuals with progressive MS.…”
Section: Benefits Of Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Skjerbaek et al 20 tested the feasibility of upper-body endurance training among 11 individuals with progressive MS who were significantly affected by the adverse effects of the disorder. The researchers found that endurance training could be performed at sufficient intensity to procure cardiovascular adaptations and therefore was feasible for individuals with progressive MS.…”
Section: Benefits Of Exercisementioning
confidence: 99%
“…13,15 During the past two decades, however, research has identified several forms of exercise with physical, emotional, and psychological benefits to individuals with MS, including Pilates, [16][17][18][19] yoga, 10,12 aquatics, 19 endurance training, 3,20 strength and cardiorespiratory training, 21 walking, 22 aerobic exercise, 23 and resistance training. [24][25][26] Exercise is now considered to be well tolerated for individuals with MS and is commonly recommended for improved physical and emotional functioning.…”
Section: Benefits Of Exercisementioning
confidence: 99%
“…In pwMS clinical symptomology affects mainly the lower limbs and reduced motor efficiency due to accompanying spasticities and motor incoordination limiting the maximum effort of the participants to a subjective felt maximum [19]. With disease onset and progressive loss of muscular functions, exercise performance and compliance to the CPET procedures on cycle ergometers becomes more difficult and impossible for pwMS with an EDSS 7.0 [20,21]. Heart rate at the lactate threshold; HR-max: Effective maximum heart rate during CPET; min: minutes; pwMS: Persons with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This dose-response relationship between the mode and the exercise intensity implicates the relevance of the exercise protocol as higher exercise intensities seem to facilitate greater benefits, also in pwMS [20,23,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Within 15-25 years of diagnosis approximately 50% of people with MS (PwMS) require the use of a walking aid [1]. Recent studies demonstrated that exercise interventions in significantly disabled PwMS resulted in endurance and strength improvement and reduction of fatigue and spasticity [2]. However engagement in long-term exercise training is limited in these patients due to multiple barriers including mobility limitation, access to an exercise facility, and cost.…”
Section: Introductionmentioning
confidence: 99%